2004
DOI: 10.1068/a36136
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Migration Model for England and Wales: Overview and Modelling Out-Migration

Abstract: The aim of the research that prompted this series of papers was to provide the Office of the Deputy Prime Minister (ODPM) with a migration modelling system, MIGMOD, potentially capable of informing the national government about policies that might have an impact on population redistribution within England and Wales. Some current concerns, for example, include: the drift of population to the South East, with concomitant increases in land pressure and house prices in that region; long-standing regional problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 6 publications
(2 reference statements)
3
44
0
1
Order By: Relevance
“…Increasing the chances of lagging is being male relative to female. This finding agrees well with those of Smallwood and Lynch (2010) and Fotheringham et al (2004). All age groups (relative to those aged 25-34) are more likely to lag in reporting.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Increasing the chances of lagging is being male relative to female. This finding agrees well with those of Smallwood and Lynch (2010) and Fotheringham et al (2004). All age groups (relative to those aged 25-34) are more likely to lag in reporting.…”
Section: Resultssupporting
confidence: 82%
“…Missing or lagging reports of address changes are identified as being greater for males than females. This observation agrees with the findings of Fotheringham et al (2004) who comment that NHSCR data are likely to undercount males, and young males, in particular.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…SIMs are particularly appropriate in the context of migration where empirical studies and model experiments have demonstrated that the propensity to migrate decreases with distance (Boyle et al, 1998;Flowerdew, 2010;Fotheringham et al, 2004;He and Pooler, 2003;Singleton et al, 2010;Stillwell, 1978;Taylor, 1983). Indeed, Olsson (1970, p. 223) notes that 'Under the umbrella of spatial interaction and distance decay, it has been possible to accommodate most model work in transportation, migration, commuting and diffusion'.…”
Section: Biproportional Fitting Modelling Methodologymentioning
confidence: 99%
“…Furthermore, the household's perceptions of the intensity of the event along with other socioeconomic aspects of everyday life, and their ability to cope and circumvent its effects, influence the adaptation strategy This model underlines the variety of mobility processes in the context of climate events through the analysis of key dimensions of spatial mobility represented by purpose, duration, frequency, composition and seasonality. These features were selected because they represent a range of characteristics that determine the nature of spatial mobility (Bell and Ward 2000;Fotheringham et al 2004). Consistent with the literature, the model identifies that mobility outcomes can be influenced by a complex interplay between exogenous factors, institutional responses and household capital.…”
Section: Towards a Conceptual Model: Integrating The Sustainable Livementioning
confidence: 79%